Design of nucleotide-mimetic and non-nucleotide inhibitors of the translation initiation factor eIF4E: synthesis, structural and functional characterisation - Soukarieh, Fadi; Nowicki, Matthew W.; Bastide, Amandine; Poyry, Tuija; Jones, Carolyn; Dudek, Kate; Patwardhan, Geetanjali; Meullenet, François; Oldham, Neil J.; Walkinshaw, Malcolm D.; Willis, Anne E.; Fischer, Peter M. (Elsevier, 2016)
Eukaryotic translation initiation factor 4E (eIF4E) is considered as the corner stone in the cap-dependent translation initiation machinery. Its role is to recruit mRNA to the ribosome through recognition of the 50 - terminal mRNA cap structure (m7 GpppN, where G is guanosine, N is any nucleotide). eIF4E is implicated in cell transformation, tumourigenesis, and angiogenesis by facilitating translation of oncogenic mRNAs; it is thus regarded as an attractive anticancer drug target. We have used two approaches to design capbinding inhibitors of eIF4E by modifying the N7 -substituent of m7 GMP and replacing the phosphate group with isosteres such as squaramides, sulfonamides, and tetrazoles, as well as by structure-based virtual screening aimed at identifying non-nucleotide cap-binding antagonists. Phosphomimetic nucleotide derivatives and highly ranking virtual hits were evaluated in a series of in vitro and cell-based assays to identify the first non-nucleotide eIF4E cap-binding inhibitor with activities in cell-based assays, N-[(5,6-dihydro-6-oxo-1,3-dioxolo[4,5-g]quinolin-7-yl)methyl]-N0 -(2-methyl-propyl)-N-(phenylmethyl)thiourea (14), including down-regulation of oncogenic proteins and suppression of RNA incorporation into polysomes. Although we did not observe cellular activity with any of our modified m7 GMP phosphate isostere compounds, we obtained X-ray crystallography structures of three such compounds in complex with eIF4E, 50 -deoxy-50 -(1,2-dioxo-3-hydroxycyclobut-3-en-4-yl)amino-N7 -methyl-guanosine (4a), N7 -3-chlorobenzyl-50 -deoxy-50 -(1,2-dioxo-3-hydroxy-cyclobut-3-en-4-yl)amino-guanosine (4f), and N7 -benzyl-50 -deoxy-50 -(trifluoromethyl-sulfamoyl)guanosine (7a). Collectively, the data we present on structure-based design of eIF4E cap-binding inhibitors should facilitate the optimisation of such compounds as potential anticancer agents.